Enabling the Rapid Development and Adoption of Speech-User Interfaces. - Kumar, Anuj; Metze, Florian; Kam, Matthew (Computer (00189162), 2014)
Speech-user interfaces offer truly hands-free, eyes-free interaction, have unmatched throughput rates, and are the only plausible interaction modality for illiterate users across the world, but they are not yet developed in abundance to support every type of user, language, or acoustic scenario. Two approaches present exciting opportunities for future research.